2022
DOI: 10.3389/fmed.2022.834887
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Long COVID-19 Symptoms After Hospital Discharge in Frail and Robust Patients

Abstract: BackgroundA motley postacute symptomatology may develop after COVID-19, irrespective of the acute disease severity, age, and comorbidities. Frail individuals have reduced physiological reserves and manifested a worse COVID-19 course, during the acute setting. However, it is still unknown, whether frailty may subtend some long COVID-19 manifestations. We explored the prevalence of long COVID-19 disturbs in COVID-19 survivals.MethodsThis was an observational study. Patients aged 65 years or older were followed-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 62 publications
3
24
1
4
Order By: Relevance
“…At the first follow up, females were by far more likely to experience persisting psychiatric and neurological symptoms following acute COVID-19, a finding in line with the open literature [ 7 , 8 , 33 ]. Moreover, females also had a significantly lower WAI at the second follow up.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…At the first follow up, females were by far more likely to experience persisting psychiatric and neurological symptoms following acute COVID-19, a finding in line with the open literature [ 7 , 8 , 33 ]. Moreover, females also had a significantly lower WAI at the second follow up.…”
Section: Discussionsupporting
confidence: 85%
“…In an online survey conducted from 6 September 2020 through 25 November 2020 on 3762 participants with confirmed COVID-19 diagnosis from 56 different countries, 203 different symptoms in 10 different organs lasting 28+ days were detected, 66 of which persisting over 7 months [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our longterm findings showed EuroQOL values almost aligned with those by others. Previous studies with a follow-up of 3 months or more indeed showed EuroQOL-index ranging from 0.61 to 0.86 [30,[34][35][36][37][38], and EuroQOL-VAS ranging from 65 to 80% [28,34,35,[38][39][40][41]. Ma et al [42] found that anxiety, depression, and pain or discomfort are the factors that most affect the long-term quality of life after COVID-19.…”
Section: Discussionmentioning
confidence: 99%